1995
DOI: 10.1002/bjs.1800820819
|View full text |Cite
|
Sign up to set email alerts
|

Ilioinguinal block dissection for malignant melanoma

Abstract: A retrospective analysis of 41 patients treated for metastatic inguinal lymph node malignant melanoma is presented: 16 underwent inguinal node excision and 25 ilioinguinal node excision. The two groups were well matched for age, sex and other characteristics. The mean time in hospital (inguinal 20 days, ilioinguinal 18 days) and the complication rates (inguinal, ten of 16 patients, ilioinguinal, 13 of 25) were similar in each group. The incidence of groin relapse, defined as the development of symptomatic mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
23
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 13 publications
6
23
1
Order By: Relevance
“…Pathologically proven superficial groin nodes are associated with a 30% to 75% 5-year survival. 4,6,31 Our 75% 5-year survival compares favorably with previous findings.…”
Section: Commentsupporting
confidence: 83%
“…Pathologically proven superficial groin nodes are associated with a 30% to 75% 5-year survival. 4,6,31 Our 75% 5-year survival compares favorably with previous findings.…”
Section: Commentsupporting
confidence: 83%
“…This approach has many advantages over the traditional procedure: less surgical trauma, no incision of the abdominal muscles or the inguinal ligament, and less postoperative pain. The postoperative hospital stay was shorter than for the traditional procedure (mean postoperative stay, 18 days) [23], and similar to that reported by Pearlman et al [16] for a modified ilioinguinal node dissection (paired oblique skin incision 4-5 cm above and below the inguinal ligament), and to that reported by Janetschek et al [9], who performed laparoscopic retroperitoneal lymph node dissection (mean postoperative hospital stay, 3.3 or 3.5 days). The number of pelvic lymph nodes retrieved by laparoscopic surgery was as expected.…”
Section: Resultssupporting
confidence: 77%
“…The standard treatment for melanoma of the lower limb is excision of the primary tumor together with lymphadenectomy in the case of lymphnode metastases [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. When groin lymph nodes are positive, pelvic lymphadenectomy should be performed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our experience with lymphoscintigraphy for sentinel node biopsy includes many cases in which lymphatic drainage flows from a low or mid-inguinal node directly to a pelvic node without passing through Cloquet's node, and hence we do not rely on the status of this node in any way in our decision making. Sterne et al [17] reported that, in their series of 25 patients, cases of multiple or fixed inguinal nodes invariably exhibited pelvic nodal disease. Therefore, although removing pelvic nodes for microscopic inguinal disease remains controversial, we believe that a superficial and deep inguinal lymphadenectomy is routinely indicated in the setting of bulky inguinal lymphadenopathy.…”
Section: Groin Dissectionmentioning
confidence: 98%